2020
DOI: 10.3390/ijerph17238900
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity Patterns of Chronic Diseases among Indonesians: Insights from Indonesian National Health Insurance (INHI) Sample Data

Abstract: Given the increasing burden of chronic diseases in Indonesia, characteristics of chronic multimorbidities have not been comprehensively explored. Therefore, this research evaluated chronic multimorbidity patterns among Indonesians using Indonesian National Health Insurance (INHI) sample data. We included 46 chronic diseases and analyzed their distributions using population-weighted variables provided in the datasets. Results showed that chronic disease patients accounted for 39.7% of total patients who attende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
11
1
1
Order By: Relevance
“…We found arterial hypertension as the most prevalent diagnosis (53.9 %), as in other studies conducted in Mexico (35), Spain (52), Italy (53), Switzerland (54), Sweden (55), and Indonesia (56). Likewise, the median number of diseases was 4 per patient.…”
Section: Discussionsupporting
confidence: 85%
“…We found arterial hypertension as the most prevalent diagnosis (53.9 %), as in other studies conducted in Mexico (35), Spain (52), Italy (53), Switzerland (54), Sweden (55), and Indonesia (56). Likewise, the median number of diseases was 4 per patient.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings provide timely evidence on the economic burden of multimorbidity in Indonesia. A study conducted by Husnayain et al found that 43% of patients who utilised secondary health care between 2015 and 2016 in Indonesia had multimorbidity [ 35 ]. Thus, our finding highlights the urgent need for policy interventions to reduce the financial burden for patients with multimorbidity in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Như vậy, nghiên cứu của chúng tôi không cho thấy sự phân biệt về bảo hiểm giữa các đối tượng khám, chữa bệnh. Kết quả này khác so với một số NC khác (có sự khác biệt giữa nam và nữ) [2], [6].…”
Section: Phân Tích Chi Phí Và Tính Công Bằng Của Bảo Hiểm Trong Khám ...unclassified